Studi keberadaan hiperparasitoid dalam mempengaruhi perilaku imago parasitoid pada kutudaun, Aphis gossypii (Hemiptera: Aphididae) - Chandra Irsan (Jurnal Entomologi Indonesia, 2008)
Study Hyperparasitoid Existing Affected to Adul Parasitoid Behavior on Aphid, Aphis gossypii (Hemiptera: Aphididae). In general, hyperparasitoid is needed for establishing food and chain webs, but in contrary, it could become a limiting factor in existing biological control program. An observation to aim positive impact of hyperparasitoid existence has been carried out. Chili plant, Capsicum annuum, Aphis gossypii, Trioxys sinensis parasitoid and Aphidencyrtus sp. were used in this observation. Results showed that hyperparasitoid existence assisted parasitoid distribution. Parasitoids were placed with hyperparasitoids enhanced parasitoid distribution or dispersion two times farther compare to without hyperparasitoids. It was concluded that dispersal behaviour of hyperparasitoid adult was a parasitoid adult’s response to avoid its suppression by the hyperparasitoid and also increase parasitoid’s searching ability.